KONDISI PERAIRAN SUNGAI DI OGAN ILIR BERDASARKAN PARAMETER FISIKA KIMIA - Elva Dwi Harmilia; Khusnul Khotimah (Jurnal Akuakultur Rawa Indonesia, 2018)
ABSTRACT The research had been done on February, March, May and April 2018 with purposive sampling method. The purpose of this research was to know condition of Ogan river waters which based on Physic and chemistry parameters. In taking sampling water was done at four stations which are desa Indralaya Mulya, desa Tanjung Seteko, and desa Muara Penimbung Ilir (Part of kecamatan Indralaya) and desa Suka Merindu (part of kecamatan Pemulutan Barat). Sampling water had been analyzed with insitu (in the field of the research) and exsitu (in laboratory). The physic parameters were brightness, turbidity, depth, DHL and TDS. The chemical parameters were: pH, DO, alkalinitas, NO2, NO3, dan NH3.  Result of the research showed that when dry weather the score of DO, pH, alkalinitas, and Nitrat become higher on May than on Februari, March, and June. Water condition of Ogan river was moderately polluted dan low fertility rate in dry weather but it still can be used for people daily used, but for fishing cultivation it only can be used for fishes which have high tolerance with bad water condition. Keywords : Physic-Chemical Parameters, Water quality, Ogan River